2013
DOI: 10.1136/jech-2013-202661
|View full text |Cite
|
Sign up to set email alerts
|

Is participation contagious? Evidence from a household vector control campaign in urban Peru

Abstract: Objectives High rates of household participation are critical to the success of door-to-door vector control campaigns. We used the Health Belief Model to assess determinants of participation, including neighbor participation as a cue to action, in a Chagas disease vector control campaign in Peru. Methods We evaluated clustering of participation among neighbors; estimated participation as a function of household infestation status, neighborhood type, and number of participating neighbors; and described report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…Some participants in both areas spontaneously remembered the Chagas campaign [48] (a door-to-door indoor residual spraying strategy) as an effective program. They described the Chagas campaign as meticulous in implementation (health workers asked and recorded details about the animals, the house, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants in both areas spontaneously remembered the Chagas campaign [48] (a door-to-door indoor residual spraying strategy) as an effective program. They described the Chagas campaign as meticulous in implementation (health workers asked and recorded details about the animals, the house, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The first detection of a rabid dog in the city of Arequipa occurred in March 2015 and by January 2016 (when our data were collected), 20 rabid dogs had been detected, of which 11 were found in Mariano Melgar. The city of Arequipa comprises communities spanning different stages of urbanization and different migration histories, from old established neighborhoods, to young neighborhoods, to recent invasions [48]. Within this gradient of development, young neighborhoods and recent invasions are often located on the periphery of the city (peri-urban area) and the older localities are nearer to the center (urban area) [38].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies on vector control have demonstrated that participation is increased when communities are engaged early in the campaign (Adalja, Sell, Bouri, & Franco, 2012; Buttenheim et al, 2014; Das, 1991); when a body of community-led promoters is engaged in the campaign (Chaki, Dongus, Fillinger, Kelly, & Killeen, 2011); when neighbouring households participate in the campaign (Bryan, Balderrama, Tonn, & Dias, 1994; Buttenheim et al, 2014); when activities are integrated into other health services and development programmes (Bryan et al, 1994; Buttenheim et al, 2014); when households are able to choose when and how to implement the control activities (Buttenheim et al, 2014; Winch et al, 1994); and when there is face-to-face contact with government officials and health workers (Buttenheim et al, 2014). To extend this body of evidence, the purpose of this study was to specifically examine motivators and barriers to participation in a Chagas disease IRS campaigns in Arequipa, Peru.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, no household was observed to be infested during both treatments of the initial treatment phase and surveillance inspections, which suggested effectiveness of the second treatment. In addition, because there is a strong correlation between infestation and participation ( 15 , 21 ), households that never participated might have initially a lower prevalence of infestation than those that participated once, in contrast to the equal prevalence we assumed in our analysis. Assuming an overly conservative 5-fold lower prevalence among never-treated houses relative to once-treated households, the never-treated households would still represent >85% of the residual infestation after the treatment phase (http://www.spatcontrol.net/articles/Barbu2014/suppMet.pdf).…”
Section: Discussionmentioning
confidence: 99%
“…Urban households have smaller peridomestic areas, fewer sources of blood, and fewer hiding places for the vector, thus mitigating some of the difficulties encountered in rural environments ( 7 , 11 13 ). However, whereas participation in control campaigns in rural areas is typically high ( 5 , 7 ), more affluent urban populations ( 14 ) might be more reluctant to participate ( 15 ). Thus, household level control might be easier in an urban household than in a rural household.…”
mentioning
confidence: 99%